(3eNJUQ SjGSI GdMQhHs - (3gQKeI Hf GYjf,J (B200 (3g` s ((3CMeO Hf ZRi GdSYOi s)
(3ChdgG (B:s
(3CYde Cf CehQ GdMQhH hMhGOKgG CcKQ hGdWa ef Cf JMjW HgG GdcJH ChJHdZgG Gdhge s
(3BNQgG (B:s
(3ef GdJbUjQ efG ai HdhZ MGLJg GdLejY hehGabJge s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B81s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B35 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI chHQjdi HGSJGfHhd (B(1294) s
(3JHUQI GdJQGLe(Bs
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs